'Museums and the display of international friendship: diplomatic interests, American philanthropy, and preserving Thomas Carlyle's London House, c. 1894.'. Issue 2 (3rd April 2021) - Hall, Melanie
ABSTRACT: It is generally recognised that towards the end of the nineteenth century the Anglo-American relationship entered a new phase characterised by friendship-building initiatives. However, as American businesses sought to expand into the British Empire's markets, that enterprise required trust more than friendship. This article captures an overlooked aspect of Ambassador Bayard's cultural diplomacy, one that sought to build trust for American products and services by harnessing American philanthropy notably through his and other prominent Americans' engagement with the Carlyle House Memorial Museum in the Empire's capital. Simultaneously, Bayard's engagement with the museum celebrated America's endorsement of international copyright legislation. It argues that Thomas Carlyle's views, together with his friendship with Ralph Waldo Emerson, made the museum-making initiative particularly suited to such purposes. At Carlyle's House, a thriving group of American ex–patriots and tourists could associate the friendship of the two authors with 'higher' ideals of a 'civilisation' held in trust.